2019
DOI: 10.1111/vru.12779
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic high resolution CT using the modified VetMousetrap™ device is a feasible method for diagnosing canine idiopathic pulmonary fibrosis in awake West Highland White Terriers

Abstract: Canine idiopathic pulmonary fibrosis is a chronic, progressive interstitial lung disease particularly prevalent in West Highland White Terriers. In the present prospective pilot study, we evaluated the feasibility of modified VetMousetrap TM device in high resolution CT to detect idiopathic pulmonary fibrosis in West Highland White Terriers. Twelve awake West Highland White Terriers with canine idiopathic pulmonary fibrosis and 24 clinically healthy West Highland White Terriers were scanned using a helical dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…In one study, motion was ranked as barely noticeable to mild in all dogs and was not statistically different between normal dogs and dogs with diseased lungs when both groups were scanned awake or with sedation. 25 In another study, a statistical difference between motion artifact present on diseased dogs scanned under sedation versus those scanned under general anesthesia was found. 33 Yet in both groups, the majority of the scans were graded as mild.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In one study, motion was ranked as barely noticeable to mild in all dogs and was not statistically different between normal dogs and dogs with diseased lungs when both groups were scanned awake or with sedation. 25 In another study, a statistical difference between motion artifact present on diseased dogs scanned under sedation versus those scanned under general anesthesia was found. 33 Yet in both groups, the majority of the scans were graded as mild.…”
Section: Discussionmentioning
confidence: 93%
“…34 Yet, recent studies demonstrated thoracic CT on sedated dogs was superior to radiographs at detecting evidence of blunt force trauma after vehicular accidents 24 and there is good agreement between abnormal CT findings and subject's clinical status in awake White Highland White Terriers with idiopathic pulmonary fibrosis. 25 Future studies should also be aimed at evaluating the indications for sedated CT scans and different sedation protocols to accommodate patients with medication limitations based on comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In canine IPF, the most common CT findings are ground-glass opacity, mosaic attenuation, and reticular patterns, while traction bronchiectasis and honeycombing are rarely described and are associated with later stages of disease [ 7 , 8 , 15 , 16 , 17 ]. Due to the paucity of correlation data between CT and histopathological patterns for ILD in the veterinary literature, histopathology of peripheral lung is the gold standard for diagnosis, as imaging results in the absence of biopsy confirmation might be misleading [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Groups 3 through 5 also have been commonly described in veterinary studies of PH, although definitive diagnosis of the underlying disease process related to PH for dogs in these groups is challenging because of the need for invasive testing including histopathology to confirm many of these disease processes. For example, pulmonary thromboembolism remains difficult to diagnose antemortem and can be found in dogs with normal d ‐dimer concentrations; tracheobronchomalacia (TBM) can require radiographic, fluoroscopic, and bronchoscopic assessment; and, pulmonary fibrosis requires histopathologic documentation, although high‐resolution computed tomography increasingly is used in the diagnosis . Clinically, PH has been reported in a number of these diseases with diagnosis based on clinical suspicion, signalment, physical examination findings, and diagnostic imaging .…”
Section: Introductionmentioning
confidence: 99%